Do Seabirds Differ from Other Migrants in Their Travel Arrangements? On Route Strategies of Cory’s Shearwater during Its Trans-Equatorial Journey - Dias, Maria P.; Granadeiro, José P.; Catry, Paulo (PLOS ONE, 2012)
Long-distance migrants have developed diverse strategies to deal with the challenges imposed by their annual journeys. These are relatively well studied in some avian groups, such as passerines, shorebirds and raptors. In contrast, few studies have addressed the migratory behaviour of pelagic birds in the light of current theories of optimal migration. Using a dataset of 100 complete migratory tracks gathered along four years, we performed a detailed study on the migratory strategy of a pelagic trans-equatorial migrant, the Cory’s shearwater Calonectris diomedea. We analysed daily routines, stopover ecology and travel speed, as well as the influence of the moon on several behavioural patterns. Cory’s shearwaters adopted a “fly-and-forage” strategy when migrating, similarly to what has been observed in some raptors. However, by flying by dynamic soaring, shearwaters attained high overall migration speeds, and were able to travel thousands of kilometres without making major stopovers and, apparently, without a noticeable pre-migratory fattening period. Other major findings of this study include the ability to adapt daily schedules when crossing major ecological barriers, and the constant adjustment of migration speed implying higher rates of travel in the pre-breeding movement, with a final sprint to the nesting colony. The present study also highlights a preference of Cory’s shearwaters for starting travel at twilight and documents a strong relationship between their migratory activity and the moon phase.